Análise de estabilidade de taludes de aterro de resíduos urbanos utilizando parâmetros geotécnicos de propostas bibliográficas e correlações com Nspt - Remédio, Flávio Henrique [UNESP] (2014)
The increase in waste generation rates, due to the increase of industrial activity and the population's purchasing power, compared to the scarcity of appropriate disposition of the waste areas, close to generating centers, has led managers to invest in increasing the capacity of load landfills in operation or reuse of old disposal areas closed to meet this demand. This leads to the construction of higher and higher landfill, reducing the problem of waste demand and, in turn, generating serious concerns over the stability of these bodies developed for studies in natural massive, with constitution and mechanical behavior of different materials disposed of in landfills. In this way, systematic studies have been performed in order to determine suitable geotechnical parameters waste present in Caetetuba Landfill, located at Atibaia/SP city. The geotechnical parameters of waste were determined based on proposals raised during the literature and based on survey results of penetration tests identified in documentary research. Several methods of slope stability analysis, raised during the literature search were evaluated to identify the most suitable method for applying the landfill Caetetuba of Health. To perform the stability analysis were prepared sections of the site, based on topographic maps and profiles polls identified in documentary research, which were implemented in SLOPE / W Geo-Slope International software. The findings were expressed in terms of security values, and compared the safety factors calculated by the various methods offered by the SLOPE / W software, depending on the variations in geotechnical parameters and analytical methods used. Within this context, the conventional slope stability calculation methods developed in soil mechanics are commonly used in the stability studies in landfills, by researchers and professionals. However, these work methodologies were